PREVENTION OF CHANGES IN THE HEMODYNAMICS OF THE UTERUS AND PLACENTA WITH INTRAUTERINE INFECTION - Rakhimova Kamola Yuldashevna (Scholar Express Journals, 2022)
Intrauterine infection of the fetus is an antenatal risk, and modern preventive measures serve to reduce the frequency of negative perinatal complications caused by intrauterine infection of the fetus.
Keywords: Fetoplacental insufficiency; intrauterine infection of the fetus; immunoprophylaxis